Does every goose count? Pitfalls of surveying breeding geese in urban areas - Kowallik, Christine; Koffijberg, Kees (Wildfowl, 2013)
The size of local breeding populations of Greylag Geese Anser anser and CanadaÂ Geese Branta canadensis at a suburban site in Northrhine-Westphalia, Germany, wasÂ assessed between 2010 and 2012 using four different methods: nest surveys, counts ofÂ territorial pairs and two types of brood counts. For both species, nest surveysÂ generated the highest estimate of breeding numbers. Geese recorded as territorialÂ pairs made up 50â€“75% of the apparent nesting pairs (73% of all nesting GreylagÂ Geese and 60% of all nesting Canada Geese in an area surveyed extensively in 2011).Â Numbers of broods recorded never exceeded 50% of the number of apparent nestingÂ pairs. Moreover, the number of broods observed was heavily dependent on fieldworkÂ intensity, with most broods found during highly frequent (twice-weekly) counts thatÂ allowed effective monitoring of the fate of individual broods, even without usingÂ individual marking. When broods are monitored less frequently, one has to rely on theÂ maximum number of broods observed simultaneously in determining the number ofÂ pairs with young, which in our study represented only 10â€“25% of the apparent nestingÂ number. Although nest counts may provide the highest estimate of breeding gooseÂ abundance, they may be impractical or undesirable (e.g. because of disturbance toÂ other breeding birds). In such cases, territorial pair assessments may be the preferredÂ method, if separation of breeding and non-breeding birds is not made tooÂ conservatively. For instance, only those birds that obviously behave as non-breeders,Â by leaving the nesting areas to feed on nearby agricultural fields during daytime, shouldÂ be excluded from breeding numbers. Although counts of the total number of broodsÂ can contribute to measures of reproductive success, they can considerablyÂ underestimate the number of goose breeding pairs.